Isolated intramuscular histoplasmosis in an elderly - diagnosis by fine needle aspiration cytology - Dr. Uma Handa; Dr. Phiza Aggarwal; Dr. Jagdish Chander; Dr. Sudhir Kumar Garg (Tropical Journal of Pathology and Microbiology, 2018)
Background: Histoplasmosis is a mycotic infection commonly affecting patients with impaired immunity. It mainly manifests as pulmonary or disseminated infection. The diagnosis is often missed in non-endemic regions due to lack of suspicion especially when it involves unusual sites in healthy individuals. Case: An elderly male presented with solitary left shoulder swelling for the last 2 months. Clinical and radiological findings were suggestive of malignant etiology. Fine needle aspiration cytology from the lesion demonstrated yeast like fungi within the histiocytes. The cytomorphological features were suggestive of Histoplasma which was later confirmed on culture. Patients had an uneventful recovery with anti-fungal treatment Conclusion: Histoplasma can present in elderly with indolent involvement of uncommon sites. High index of suspicion accompanied by active search using special stains is the key to diagnosis